Faktor-Faktor Yang Mempengaruhi Kejadian Hipertensi di RSUD Toto Kabila Kabupaten Bone Bolango - Nikmawati Puluhulawa; Nurliah; Avriliani Sagita Molou (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Hypertension is a condition where there is an abnormal increase in blood pressure in arteries and occurs continuously. The purpose of the study was to determine affecting incidence of hypertension. This study uses an Analytical Survey research with a Cross Sectional design. Total sampling technique was used in taking the sample, with a total of 23 respondents. Data collection techniques used a questionnaire. The results showed age factor with p value =0.068 (> 0.05), obesity factor with p value = 1,000 (< 0.05), history of diabetes mellitus factor with p value = 0.253 (< 0.05). It was found that there was an influence of age on the incidence of hypertension and there was no effect of obesity and a history of diabetes mellitus on the incidence of hypertension.